2019
DOI: 10.1177/0021998319855765
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable mineral coating of alkali-resistant glass fibres in textile-reinforced mortar composites for structural purposes

Abstract: The mechanical performance of a silica-based mineral nano-coating applied to alkali-resistant glass textile-reinforced composite materials aimed at structural strengthening is investigated experimentally. The silica nano-film is directly applied to the alkali-resistant glass fabric by sol–gel deposition. Two lime mortars are adopted as embedding matrix, which differ by the ultimate compressive strength and elongation. Uni-axial tensile tests of prismatic coupons are carried out according to the ICC AC434 guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…In the case of MIII, the amelioration of the adherence between SSG and mortar could be explained through the pozzolanic reaction where the fly ash can react with portlandite in presence of water to form more CSH and thus reduces the macro-pores. This results in high bonding capacity as reported by Signorini et al [23] and Butler et al [13].…”
supporting
confidence: 64%
See 1 more Smart Citation
“…In the case of MIII, the amelioration of the adherence between SSG and mortar could be explained through the pozzolanic reaction where the fly ash can react with portlandite in presence of water to form more CSH and thus reduces the macro-pores. This results in high bonding capacity as reported by Signorini et al [23] and Butler et al [13].…”
supporting
confidence: 64%
“…It was found that the addition of fly ash to cement at higher replacement level (65%) produced a better deformation capacity than the one obtained in the case of cement replaced by fly ash at lower replacement level (42%). Signorini et al [ 23 ] researched the tensile behaviour of TRM made with glass textile coated by silica-based mineral and lime mortars. Tow lime mortars with large and small macro-pores were used to prepare the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Two different multifilament fabrics are considered as the reinforcing phase (Figure 1 alcohol solution together with nitric acid in stoichiometric ratio to trigger solgel transition, see also [46]. The silica solution, with an overall CNT weight ratio of 0.5%, is stirred for 2 hours at 50 • C and then sonicated for further 15 minutes before fibres' dip-coating.…”
Section: Methodsmentioning
confidence: 99%
“…These ions are accelerated in the electric field to obtain energy, which can lead to the growth of thin film at low temperature [14]. SiO 2 is the most favored inorganic material and has been widely applied because of its excellent chemical stability, mechanical strength, and high transparency [15]. In this work, SiO 2 was coated onto silk fabric by PECVD, and a robust superhydrophobic SiO 2 @silk fabric was further constructed by HMDS modification.…”
Section: Introductionmentioning
confidence: 99%
“…Compared 186 with bare silk, the transmittance of the SF-nSiO2 are lower, and the UPF values of the SF-nSiO2 are 187 higher, exhibiting excellent UV resistance properties. The results show that amorphous SiO2 plays an 188important role in the diffusion barrier layer and the passivation layer[15]. In addition, we measured 189 the K/S values of bare silk and SF-nSiO2 before and after UV light irradiation, as shown inFigure 1905c,d.…”
mentioning
confidence: 97%